Posterior Reversible Encephalopathy Syndrome during Pregnancy: A Case Report - Mirzamoradi, Maasoumeh; Rahmati, Nayyereh; Khandani, Ayda; Rezaei Aliabad, Nahid; Parsa, Yekta (Novelty in Biomedicine, 2020)
Background: Posterior reversible encephalopathy syndrome (PRES) is a neurological condition entity presenting with headache, confusion, seizure, altered mentation and loss of vision associated with white matter changes on imaging. The lesions in PRES are thought to be due to vasogenic edema, mainly in the posterior cerebral hemispheres. Cases Report: This study has reported a patient who developed PRES without any indicators for preeclampsia-eclampsia in her pregnancy. The patient’s brain images showed abnormal signal intensity in the occipital lobe. Conclusion: Posterior reversible encephalopathy syndrome is reversible when initial diagnosis established and suitable treatment start immediately.